114k views
5 votes
Enter the value x that makes the equation 7x-4+8x-3=-67

X=

User Thednp
by
4.4k points

2 Answers

5 votes

x = -4

Step-by-step explanation:

  1. Collect the like the terms: 15x - 4 - 3 = -67
  2. Calculate the difference: 15x -7 = -67
  3. Move constant to the right side and change its sign: 15x = -67 +7
  4. Calculate the sum: 15x = -60
  5. Divide both sides of the equation by 15: x = -4
User Justin Ryder
by
4.6k points
2 votes

7x-4+8x-3x=-67

Combine the x’s

12x-4=-67

Bring the -4 under the -67 and make it positive

Add the 4 and -67

12x=-63

Put division signs under bothering numbers and divide by 12. The 12x/12 would cancel out to be x.

Divide -67/12

X=-5.25

User David Dossot
by
4.8k points